Transmission of SARS-CoV-2 in the household setting: a prospective cohort study in children and adults in England - Miller, E; Waight, PA; Andrews, NJ; McOwat, K; Brown, KE; Katja, H; Ijaz, S; Letley, L; Haskins, D; Sinnathamby, M; Cuthbertson, H; Hallis, B; et al. (Elsevier, 2021)
Objectives To measure secondary attack rates (SARs) in prospectively followed household contacts of paediatric and adult cases of SARS-CoV-2 infection in England. Methods Self-taken nasal swabs from household contacts of PCR confirmed cases of COVID-19 and blood samples on day 35 were tested for evidence of infection with SARS-CoV-2 virus. Results The secondary attack rate (SAR) among 431 contacts of 172 symptomatic index cases was 33% (95% confidence intervals [CI] 25–40) and was lower from primary cases without respiratory symptoms, 6% (CI 0–14) vs 37% (CI 29–45), p = 0.030. The SAR from index cases <11 years was 25% (CI 12–38). SARs ranged from 16% (4–28) in contacts <11 years old to 36% (CI 28–45) in contacts aged 19–54 years (p = 0.119). The proportion infected who developed symptoms (78%) was similar by age (p = 0.44) though <19 year olds had fewer mean number of symptoms than adults (p = 0.001) and fewer reported loss of sense of taste or smell (p = 0.0001). Conclusions There are high risks of transmission of SARS-CoV-2 virus in the home, including those where infection is introduced by a child. The risk of children acquiring infection was lower than that in adults and fewer developed typical symptoms of Covid-19 infection.